Analisis Bentuk dan Struktur Komposisi â€œMorning Happinessâ€ Gus Teja - I Made Jacky Ariesta; Ni Wayan Ardini; I Komang Darmayuda; Ketut Sumerjana (Journal of Music Science, Technology, and Industry, 2018)
Gus Teja World Music’s musical composition "Morning Happiness" (2008) was inspired when its composer Agus Teja Sentosa (Gus Teja) had been suddenly stunned to see his child smile after being recovered from illness in one morning. The sounds of happiness or the morning bliss was then poured into the instrumental musical composition which was put in his group’s first album "Rhytm of Paradise". The problem of this research is how the form and structure of the composition was. The research method used is qualitative. The theory used to solve the problem is the form and structure analysis theory of song. Primary data sources were obtained from interviews, observations, and discography (VCD). Secondary data were obtained from books, journals, and internet sources. The result of the research showed the musical instruments used in this composition, are flute, selokro, tingklik baro, guitar, bass, kendang angklung. In this composition, the flute plays an important role as the main melody of the song. The instruments are made from bamboos, and the flute used in this composition is a blend of Balinese flute with Indian and Bandung ones. From the musical aspects, there are rules such as the provisions of number of bars, sukat, progress chord in which rhythm patterns are played in accordance with what are usually determined. This composition uses the basic tone D = do, with an allegro tempo (120MM), and uses a ¾ and a three-part shaped A, B, C, C', started with an introduction.